The Effect of Servant Leadership on Work Engagement: The Mediating Role of Employee Resilience, Organizational Support, and Self-Efficacy - Bethari Ardra Larissa; Suyono, Joko (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of servant leadership on work engagement through employee resilience, organizational support, and self-efficacy. This quantitative study uses a cross-sectional survey design involving 235 permanent employees in construction industry in the Special Region of Yogyakarta, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that servant leadership positively affects work engagement, both directly and indirectly. These findings show that servant leadership plays a significant role in enhancing employees’ work engagement, both through direct influence and through the mediating roles of employee resilience, organizational support, and self-efficacy. Keywords: Servant Leadership; Work Engagement; Employee Resilience; Organizational Support; Self-Efficacy; Construction Industry